PENGATURAN PROSEDUR DALAM PENANGANAN UNJUK RAJA OLEH BRIMOB - I Wayan Eka Artajaya (Universitas Mahendradatta, 2025)
The legal responsibility of Brimob members in carrying out their duties isalso a crucial topic in the context of legal protection. In tense situations, Brimob's useof force must always be within legal limits. Numerous cases have seen Brimob membersface legal action for perceived excessive use of force, whether in the form of physicalviolence or human rights violations. Therefore, there is a need for clear legalprotection for Brimob members, which not only protects them from legal action butalso ensures that their actions comply with applicable human rights principles inIndonesia.